Study of risk factors and tumor markers in ovarian malignancy in western part of Odisha: a prospective observational study - Pradhan, Hemanta Kumar; Singh, Pratibha; Ravikumar, M. S.; Gothwal, Meenakshi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Ovarian cancer represents one of the most frequently seen malignancies in women and it is the fifth most common cause of cancer-related death in women. The aim of the study to determine the risk factors leading to ovarian cancer in western part of Odisha, India and show the tumour markers in this population. Methods: This is a prospective observational study included 240 ovarian masses diagnosed at Department of Obstetrics and Gynaecology, V. S. S. Medical College, Burla, Sambalpur over 3 years based on preoperative clinical, biochemical (tumour markers) and imaging study and confirm through post-operative histopathology reports. Results: Surface epithelial tumours (68.33%) followed by germ cell tumours (30.83%) are the most common ovarian tumour. Incidence of ovarian cancer is 73.58% in ≤50 years of age group and more number of cases (16.65%) also found in younger age (≤30 year). Overall number of ovarian cancer cases rising. Bilateral tubal ligation is not a protective factor for ovarian cancer (p value >0.05) and consumption of alcohol and tobacco is not increase risk for ovarian cancer. Most of ovarian tumour commonly present with vague abdominal pain (75.83%) followed by mass per abdomen (55%). Ascites mainly a presentation of malignant tumour seen in 46(63.88%) cases. CA125 is the frequently detected tumour markers and all of the tumour markers were significantly within normal limit. Conclusions: Ovarian neoplasia is one of the most common and lethal malignancy in female reproductive tract. Though it is a disease of older age but now a day more no of cases also seen in younger age group. Since most of the ovarian cancer remain asymptomatic for long period so measure should be taken for early diagnosis for best outcome. So, assessment of each regions statistical information reflecting its own profile may be important for estimation of risk for development of ovarian cancer and so useful for early preventive measure before progress to advance stage where prognosis is worst. So, relationship between the profiles of patients and types of ovarian neoplasms may give an idea about the risk factors of the disease in its region. Additionally, distribution of tumour markers might be considered for the dis-criminating of the benign or malign characters of the ovarian neoplasia.